Crystal orientation-induced Al grain coalescence coarsening during isothermal semisolid annealing of Al-15 wt% Cu alloys under high magnetic fields - Siyu Zhang; Tie Liu; Baoze Zhang; Alexander Dahlström; Sinuo Li; Kai Wang; Wangzhong Mu; Qiang Wang (Journal of Materials Research and Technology)
Al-15 wt% Cu binary alloys were isothermally annealed in a semisolid state with and without a 10 T magnetic field. The influence of the magnetic field on the 2D morphology and 3D distribution of α-Al grains was investigated. The coarsening mechanism under a high magnetic field was proposed based on microstructural analysis, coarsening kinetics calculations, and interfacial energy calculations. The size of the α-Al grains was increased, and the coarsening rate was significantly accelerated by the magnetic field. Meanwhile, more α-Al grains contacted each other and started coalescing. The grain size distribution revealed that the coarsening mechanism shifted from Ostwald ripening at 0 T to a combination of the Ostwald ripening and migration-coalescence at 10 T. The accelerated coarsening rate may be attributed to an increase in interfacial energy from 0.143 to 0.213 J m−2 under the high magnetic field. Significant Cu clustering was observed between coalesced grains at 10 T, which could further demonstrate the accelerated coarsening rate. Additionally, the magnetic field induced the rotation of adjacent grains via magnetic torque, reducing their misorientation and subsequently enhancing their coalescence. This study elucidated the mechanism of orientation-induced grains coarsening under a high magnetic field, providing a novel methodology for controlling metallic materials fabrication processes which undergo grains coarsening using magnetic fields.